2014
DOI: 10.1149/2.0601409jes
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline Vanadium Oxide Nanorods: Growth, Structure and Improved Electrochemical Response as a Li-Ion Battery Cathode Material

Abstract: Thermally removing amine molecules that serve as chemical templates for vanadium oxide nanotubes is demonstrated to significantly improve the performance when tested as a cathode material in Li-ion battery cells. Capacity fading issues associated with blocked intercalation sites on the (010) faces of layered vanadium oxide that form the nanotubes are prevented. Thermal treatment of the nanotubes up to 600 • C is shown to cause a specific conversion from nanotubes to polycrystalline nanorods and removal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 103 publications
(160 reference statements)
1
18
1
Order By: Relevance
“…V 2 O 3 poly‐NRs were prepared by annealing vanadium oxide (V 2 O 3 nanotubes (VONTs) as previously reported . Briefly, VONTs were synthesized via hydrothermal treatment of a vanadium oxide xerogel mixed with nonylamine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…V 2 O 3 poly‐NRs were prepared by annealing vanadium oxide (V 2 O 3 nanotubes (VONTs) as previously reported . Briefly, VONTs were synthesized via hydrothermal treatment of a vanadium oxide xerogel mixed with nonylamine.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the structure defining role of the amines in the synthesis of the VONTs, they are detrimental to their electrochemical performance . We have previously reported on the poor electrochemical performance of as prepared VONTs, which achieved capacities <10 mAh g −1 . We demonstrated that the amine molecules which occupy the majority of the possible lithium intercalation sites within the VONTs are responsible for the poor cycling performance and that removing the amines via thermal treatment can significantly improve electrochemical performance.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These demands have necessitated studies into the development of active materials with higher specific capacities and enhanced cycle-lives678. From the perspective of anode materials for Li-ion applications, these can be broadly divided into three classes based on the reactions occurring during lithiation/delithiation namely; intercalation mode, alloying mode and conversion mode materials91011.…”
mentioning
confidence: 99%
“…The layered geometry of orthorhombic crystalline V 2 O 5 makes it ideally suited to the reversible intercalation of mobile guest species, 21,22 such as Li + and other cations. [23][24][25][26] While the lattice structure is theoretically maintained upon mild intercalation, phase changes are known to occur and the interlayer van der Waals spacing characteristic of its layered orthorhombic crystal structure can become deformed at lower voltages (higher Li mole fraction). 27,28 Large particle sizes can also limit the solid state diffusional rate of cation insertion.…”
mentioning
confidence: 99%